Antagonistic and plant growth promoting properties of actinomycetes from rhizosphere Deschampsia antarctica È. Desv. (Galindez Island, Antarctica) - Tistechok, S.; Skvortsova, M.; Luzhetskyy, A.; Fedorenko, V.; Parnikoza, I.; Gromyko, O. (Український антарктичний журнал, 2019)
Aim. The isolation of actinomycetes from Deschampsia antarctica É. Desv. (Galindez Island, Antarctica) rhisosphere and determine their ability to produce compounds with antimicrobial and plant growth promotional properties.